Improving public acceptance of H2 stations: SWOT-AHP analysis of South Korea - Lee, Youhyun; Kim, Young Jin; Lee, Min Chul (International Journal of Hydrogen Energy, 2021)
Green and sustainable transportation has emerged as a mandatory task in alignment with climate change issues globally. In South Korea, fuel cell hydrogen vehicles (FCEVs) are considered to be an alternative to manage the global climate change paradigm and for local fine dust problems. However, low public acceptance is the greatest barrier to the growth of FCEVs and the hydrogen economy. To address this issue, this article discusses possible strategies for enhancing public acceptance of H2 stations using SWOT-AHP methodology and an additional focused group interview. As a result, the strength factor was the highest 1st class priority factor. In the 2nd class, the SO and ST strategies are highly recommended for enhancing public acceptance of H2 infrastructure. This article concludes with practical policy suggestions and alternatives, highlighting the importance of active research and development for hydrogen safety and the need for government-driven support.
Keywords: Fuel cell electric vehicle; Global climate changes; Green transportations; H2 station; Hydrogen economy; Hydrogen vehicles; Public acceptance; South Korea; Sustainable transportation; SWOT-AHP; Fuel cell electric vehicle (FCEV); H2 station; Hydrogen economy; Public acceptance; SWOT-AHP